2021
DOI: 10.1140/epjp/s13360-021-01104-9
|View full text |Cite
|
Sign up to set email alerts
|

Traversable wormholes with vanishing sound speed in f(R) gravity

Abstract: We derive exact traversable wormhole solutions in the framework of f(R) gravity with no exotic matter and with stable conditions over the geometric fluid entering the throat. For this purpose, we propose power-law f(R) models and two possible approaches for the shape function b(r)/r. The first approach makes use of an inverse power-law function, namely $$b(r)/r\sim r^{-1-\beta }$$ b ( r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Frequently, "exotic" matter contributions seem to be needed to describe hypothetical objects that are massive and compact, in order to fulfill stability criteria. Similar examples can often be found for wormholes and cosmological backgrounds [12][13][14], and likely exotic matter could indicate a possible signature of general relativity's breakdown [15,16].…”
Section: Introductionsupporting
confidence: 60%
“…Frequently, "exotic" matter contributions seem to be needed to describe hypothetical objects that are massive and compact, in order to fulfill stability criteria. Similar examples can often be found for wormholes and cosmological backgrounds [12][13][14], and likely exotic matter could indicate a possible signature of general relativity's breakdown [15,16].…”
Section: Introductionsupporting
confidence: 60%
“…can be found in the literature. [ 18–26 ] In a recent work physically viable wormhole solutions in the f(R) theory of gravity with exponential model have been discussed by Mustafa et al. [ 30 ] Recently, Falco et al.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Classical works comprising the modified theory of f (R) gravity by Capozziello et al can be found in the literature. [18][19][20][21][22][23][24][25][26] In a recent work physically viable wormhole solutions in the f (R) theory of gravity with exponential model have been discussed by Mustafa et al [30] Recently, Falco et al have discussed the wormhole solutions through the Poynting-Robertson effect. [27,28] Non-extremal spherically symmetric instanton wormhole solution in string theory have been discussed by Bergshoeff et al [31] Maldacena et al have presented a study of some traversable wormhole geometries in the background of AdS 2 gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Capozziello et al [39] derived the exact traversable WH solutions as well as stable conditions in the absence of exotic matter in f (R) theory and found that small deviation from GR give stable solutions. De Falco et al [40] formulated the static spherically symmetric WH solutions in the same framework.…”
Section: Discussionmentioning
confidence: 99%